Cointegration Analysis in an Inflationary Environment: What Can We Learn from Ukraine's Nominal Exports? - Hubert Strauß (Kiel Institute of World Economics (IfW), 2001)
Ukrainian exports can be explained by standard demand theory in the long run. Using the Johansen procedure the data do not reject the hypothesis of a unit foreign-production elasticity of Ukrainian exports, which are rather price-elastic inputs for foreign producers. It is argued that due to high domestic inflation and substantial real appreciation of the hryvnia there might be a deterministic element in the long-run relationships. When allowing for a trend in the cointegration space, the identifying restriction of an infinitely price-elastic export supply curve produces best results. However, due to missing export price statistics long-run interpretations are to be taken with care because they are conditional upon assumptions on how costs and exchange-rates are passed through on export prices.
Keywords: F17; F31; F41; P33; 330; cointegration analysis; transitional economies; Ukraine; export demand; foreign trade elasticities; real effective exchange rate; Export; Nachfrage; Außenhandelselastizität; Kointegration; Schätzung; Kaufkraftparität; Inflation; Exchange rate pass-through; Ukraine